(untitled) (Itinera, 2024)
At its core, documentary photography is characterized by its value as a document and a testimony that also carries expressive and aesthetic significance. Specifically, these as- pects are in concordance when depicting situations characterized by suffering and social distress (e.g. poverty). In these contexts, the choices made in regards to the positioning and distance of the observing gaze involve a mutual interplay between ethics and aesthet- ics. This article proposes a critical evaluation of the showcasing distress – which is also a focal point of a recent period of cinematographic critique in Europe –, and provides an outline for an “aesthetic of boundaries” through theoretical and field-based contributions.